Enhancing the resilience of sustainable supplier management through the combination of win‒win lean practices and auditing mechanisms—An analysis from the resource-based view - Qin, Zhixia; Chen, Ping-Kuo (Frontiers in Environmental Science, 2022)
The purpose of this study is to explore when win‒win lean practices can be combined with auditing mechanisms, specifically when adopting the combination of the two. In it, we investigate which capabilities are produced and how they build a stronger control system and produce a greater control force for supplier involvement in the development of the lean practices environment. Does the control force have a positive effect on raising resilience and further realizing the targets of sustainable supplier management? The resource-based view (RBV) is an important theoretical basis for this study. Covariance-based Structural Equation Modelling (CB-SEM) is the main method applied to analyse data from 231 Chinese manufacturers to test and verify the research questions. To test and verify the research questions with CB-SEM before, we test and measure the validity and reliability of the constructs through factor loadings, composite reliability (CR), and average variance extracted (AVE). In addition, we also verify the discriminant validity through the Fornell-Lacker criterion and Cross Loadings and test the multicollinearity. We use AMOS and SPSS 23.0 as our analysis tools. According to the test results, win‒win lean practices can increase supplier dependence on leading companies or manufacturers. It can drive supplier involvement in the formulation of a lean practice environment, expand control over suppliers, produce greater visibility, and further have a positive effect on resilience. In addition, when combined with auditing mechanisms, dependency will drive suppliers to cooperate with auditing practices and reduce their resistance, increase their involvement in the formulation of lean practice environments, further promoting resilience. In addition, dependency and auditing intervention will induce or even raise stakeholder pressure, which can usually maintain the supplier’s cooperation. Finally, dependence, positive intervention, and stakeholder pressure can be deemed strategic resources or capabilities. Based on the above, a cycle between three will be formulated and become a stronger control system, producing greater control force to continue maintaining supplier involvement. It will produce a positive effect to enhance resilience and further realize sustainable supplier management.